Hubungan Self-esteem dengan Self-presentation pada Remaja Pengguna Instagram - Ela Anriani Putri; Wilda Ansar; Andi Nahliah Bungawali (Scidacplus, 2026)
In today's digital era, teenagers are increasingly active in using social media, one of which is Instagram. Teenagers who use Instagram are vulnerable to decreased self-esteem due to social comparison and validation seeking, so they tend to present an ideal and different self to appear attractive. This causes a mismatch between the real self and the self on Instagram, as well as the pressure to always appear perfect. This study aims to analyze the relationship between self-esteem and self-presentation in adolescent Instagram users in Makassar. This study used a quantitative method with 398 adolescents as respondents. The analysis technique used was the Spearman rho correlation test. Based on the results of the data analysis, there was a positive relationship between self-esteem and ideal self, consistent self, and multiple selves, while online presentation preferences were negatively related. This indicates that the higher the level of adolescent self-esteem, the higher the tendency to engage in ideal self, consistent self, and multiple selves on Instagram. However, self-esteem and online presentation preferences had a negative relationship. The implications of this study emphasize the importance of monitoring social media use and strengthening self-esteem so that adolescents are able to understand social pressures on Instagram and present themselves consistently with their personal character.